Diagnosis of Peripheral Pulmonary Lesions with Transbronchial Lung Cryobiopsy by Guide Sheath and Radial Endobronchial Ultrasonography: A Prospective Control Study. (28th September 2021) - Jiang, Ling; Xu, Jian; Liu, Chunfang; Gao, Na; Zhao, Jing; Han, Xue; Zhang, Xiaolin; Zhao, Xiaohui; Liu, Yuan; Wang, Weixue; Zhao, Junjun
Abstract : Objective . We design a prospective control study on the utilization of transbronchial cryobiopsy guided by EBUS-GS (EBUS-GS-TBCB) to diagnose PPLs. Methods . PPLs were defined as pulmonary nodules or masses with a diameter from 10 mm to 50 mm. PPLs were randomly divided into group EBUS-GS-TBCB and transbronchial biopsy by forceps guided under EBUS-GS (EBUS-GS-TBB). Results . 28 cases were involved in group EBUS-GS-TBCB and 31 cases were in group EBUS-GS-TBB. The mean sizes of PPLs were 30.23 ± 11.10 mm in group EBUS-GS-TBCB and 28.69 ± 8.62 mm in group EBUS-GS-TBB ( t = 0.600, p = 0.551 ). The diagnostic yields of EBUS-GS-TBCB and EBUS-GS-TBB were 75% and 64.52% respectively, and the difference between the two groups was not significant ( χ 2 value = 0.137, p = 0.711 ). If only the first specimen was taken into account, the diagnostic yields from EBUS-GS-TBCB and EBUS-GS-TBB were 64.29% (18/28 cases) and 35.48% (11/31 cases), respectively. The difference was statistically significant by Fisher's Exact Test ( χ 2 value = 4.883, p = 0.038 ). The total incidence rates of bleeding were 21.43% and 6.45%, respectively, in groups EBUS-GS-TBCB and EBUS-GS-TBB. The total incidence rates of pneumothorax were 7.14% and 0, respectively, in groups EBUS-GS-TBCB and EBUS-GS-TBB. Conclusion . The diagnostic yield of EBUS-GS-TBCB was slightly higher than that of EBUS-GS-TBB for the diagnosis of PPLs. EBUS-GS-TBCB might be useful if only the first sample was taken into account.